Providing for the Casualties of War The American Experience Through World War II - Rostker, Bernard D. (RAND Corporation, 2013)
War has always been a dangerous business, bringing injury, wounds, and death, and--until recently--often disease. What has changed over time, most dramatically in the last 150 or so years, is the care these casualties receive and who provides it. This book looks at the history of how humanity has cared for its war casualties and veterans, from ancient times through the aftermath of World War II.